Medical education system in Malaysia maintaining a gold standard – an extraordinary example from the Malaysian Society of Pharmacology and Physiology - Roy, Bedanta; Goh, Nicholas; Malik, Rukhsana Hussain (Nepal Journal of Epidemiology, 2018)
Founded in 2011 Quest International University Perak (QIUP) is a private university in partnership with Perak state Government. Various professional programmes are conducted in Faculty of Medicine (FOM) helps the young lecturers. Enormous financial aids and moral support are provided by the University for competitive events which are highly appreciable. Universities across the world should encourage their faculties, to organize and participate healthy competitions like quiz, teachers’ prize to make a better educator who guides future health care professionals. Nepal J Epidemiol. 2017;7(3); 697-698